The Role of Auditor Narcissism in Auditor‐Client Negotiations: Evidence from China - Church, Bryan K.; Dai, Narisa Tianjing; Kuang, Xi (Jason); Liu, Xuejiao (Contemporary Accounting Research, 2020)
ABSTRACT This paper reports the results of three studies (archival, experimental, and qualitative) designed to examine the effects of auditor narcissism on auditor‐client negotiations in China. We contend that narcissistic characteristics fuel auditors' competitiveness and embolden them to stand firm in negotiations, potentially lengthening the negotiation process but leading to more conservative negotiation outcomes. As predicted, our archival results suggest that auditor narcissism is positively associated with audit delay and negatively associated with clients' absolute and positive discretionary accruals. Our experimental results document that narcissistic auditors are more likely to be involved in negotiations that reach an impasse or take longer to resolve and that narcissistic auditors negotiate reported asset values that reflect less aggressive reporting choices. Our qualitative results from field interviews with practicing audit partners corroborate our archival and experimental findings. Overall, the data collected using three different research methods yield consistent results in support of our theory. Our findings shed light on factors that influence audit efficiency and quality in China. We discuss the key cultural and contextual differences between China and the West as well as the implications of these differences for future research.